Regularity of a renewal process estimated from binary data. Issue 2 (9th October 2017) - Rice, John D.; Strawderman, Robert L.; Johnson, Brent A.
Summary: Assessment of the regularity of a sequence of events over time is important for clinical decision‐making as well as informing public health policy. Our motivating example involves determining the effect of an intervention on the regularity of HIV self‐testing behavior among high‐risk individuals when exact self‐testing times are not recorded. Assuming that these unobserved testing times follow a renewal process, the goals of this work are to develop suitable methods for estimating its distributional parameters when only the presence or absence of at least one event per subject in each of several observation windows is recorded. We propose two approaches to estimation and inference: a likelihood‐based discrete survival model using only time to first event; and a potentially more efficient quasi‐likelihood approach based on the forward recurrence time distribution using all available data. Regularity is quantified and estimated by the coefficient of variation (CV) of the interevent time distribution. Focusing on the gamma renewal process, where the shape parameter of the corresponding interevent time distribution has a monotone relationship with its CV, we conduct simulation studies to evaluate the performance of the proposed methods. We then apply them to our motivating example, concluding that the use of text message reminders significantly improves the regularity of self‐testing, but not its frequency. A discussion on interesting directions for further research is provided.